2015
DOI: 10.4149/bll_2015_014
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of GSTP1, APC and RASSF1 gene promoter hypermethylation in urine DNA of prostate-diseased patients

Abstract: Objectives: Prostate cancer (PCa) represents one of the most complicated human tumors and, like many others malignancies, arises from progressive genetic and epigenetic alterations. Among all recognized epigenetic alterations, aberrant DNA methylation (hypo-and hypermethylation) is the most important and the best characterized change in PCa. Background: We analyzed GSTP1, APC and RASSF1 gene promoter hypermethylation in urine DNA of ten previously non-treated prostate-diseased patients. Methods: For the purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Prior to treatment, all patients underwent a computed tomography (CT) scan of the chest, abdomen and pelvis, bone scans, a physical examination, esophagography, upper gastrointestinal endoscopy and, if necessary, 18F-fluorodeoxyglucose-positron emission tomography. Patients were staged according to the Tumor-Node-Metastasis system of the American Joint Committee on Cancer (2009) (12) and the International Union Against Cancer (2002) (14) as follows: 6 patients (7.9%) were stage T1; 37 (48.7%) were T2; 33 (43.4%) were T3-4. A total of 54 patients also had lymph node (LN) metastasis: 26 patients were stage I–II; 50 patients were stage III–IV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to treatment, all patients underwent a computed tomography (CT) scan of the chest, abdomen and pelvis, bone scans, a physical examination, esophagography, upper gastrointestinal endoscopy and, if necessary, 18F-fluorodeoxyglucose-positron emission tomography. Patients were staged according to the Tumor-Node-Metastasis system of the American Joint Committee on Cancer (2009) (12) and the International Union Against Cancer (2002) (14) as follows: 6 patients (7.9%) were stage T1; 37 (48.7%) were T2; 33 (43.4%) were T3-4. A total of 54 patients also had lymph node (LN) metastasis: 26 patients were stage I–II; 50 patients were stage III–IV.…”
Section: Methodsmentioning
confidence: 99%
“…High XRCC1 expression levels are associated with resistance to RT in patients with gastric, ovarian, lung, head and neck cancer (911). Previous studies have revealed that the expression of RASSF1 transcripts and the degree of methylation are associated with tumor progression and with the survival rate in patients with ESCC (12,13); however, few studies have been conducted on the radiosensitivity effects of RASSF1 in ESCC. In the present study, a retrospective analysis was performed of the expression patterns of COX-2, XRCC1 and RASSF1 in pre-treatment endoscopic biopsy tissue specimens from patients with ESCC, using immunohistochemical staining.…”
Section: Introductionmentioning
confidence: 99%
“…15 GSTP1 and RASSF1 are two genes whose expression in healthy and cancerous groups has been discussed in various articles on the incidence and progression of prostate cancer. 16 It is shown that the expression of these genes is affected by changes in the methylation pattern through which their expression is reduced by hypermethylation. 17 Therefore, they are among the candidate genes as biomarkers for early detection of prostate cancer in Kashmir, Vietnam, and a large number of other populations.…”
Section: Dovepressmentioning
confidence: 99%
“…17 Therefore, they are among the candidate genes as biomarkers for early detection of prostate cancer in Kashmir, Vietnam, and a large number of other populations. 16,18,19 Inês Graça (2016) stated that potential therapeutic agents for managing prostate cancer are epigenetic changes of the disease which highlights the important role of epigenetic modulators in pre-trial and clinical trials. 20 In addition, it is well understood that HDAC, DNMT3A, and DNMT3B are major epigenetic factors regulating methylation patterns of GSTP1 and RASSF1 genes which alter the expression of the genes in prostate cancer.…”
Section: Dovepressmentioning
confidence: 99%
“…DNA methylation provides a stable mechanism of gene repression that is responsible for the loss of activity of tissue-specifi c genes, genes on the X chromosome, and gene imprinting during the development, as well as in differentiated tissues of the organism (21,22). DNA methylation is inherited through cell division in a symmetrical manner.…”
Section: Discussionmentioning
confidence: 99%